Protein O-GlcNAc Modification Increases in White Blood Cells After a Single Bout of Physical Exercise - Nagy, Tamás; Kátai, Emese; Fisi, Viktória; Takács, Tamás Tibor; Stréda, Antal; Wittmann, István; Miseta, Attila (Frontiers in Immunology, 2018)
Background: Protein O-linked N-acetylglucosamine (O-GlcNAc) is a dynamic post-translational modification influencing the function of many intracellular proteins. Recently it was revealed that O-GlcNAc regulation is modified under various stress states, including ischemia and oxidative stress. Aside from a few contradictory studies based on animal models, the effect of exercise on O-GlcNAc is unexplored. Purpose: To evaluate O-GlcNAc levels in white blood cells (WBC) of human volunteers following physical exercise. Methods: Young (age 30±5.2), healthy male volunteers (n=6) were enlisted for the study. Blood parameters including metabolites, ions, “necro”-enzymes and cell counts were measured before and after a single bout of exercise (2 mile run). From WBC samples, we performed western-blots to detect O-GlcNAc modified proteins. The distribution of O-GlcNAc in WBC sub-populations was assessed by flow cytometry. Results: Elevation of serum lactic acid (increased from 1.3±0.4 mM to 6.9±1,7 mM), creatinine (from 77.5±6.3 U/L to 102.2±7.0 µM) and lactate dehydrogenase (from 318.5±26.2 U/L to 380.5±33.2 U/L) confirmed the effect of exercise. WBC count also significantly increased (from 6.6±1.0 G/L to 8.4±1.4 G/L). The level of O-GlcNAc modified proteins in WBCs showed significant elevation after exercise (85±51%, p<0.05). Flow cytometry revealed that most of this change could be attributed to lymphocytes and monocytes. Conclusion: Our results indicate that short term exercise impacts the O-GlcNAc status of WBCs. O-GlcNAc modification could be a natural process by which physical activity modulates the immune system. Further research could elucidate the role of O-GlcNAc during exercise and validate O-GlcNAc as a biomarker for fitness assessment.